Non-cognitive skills and immigrant-native inequalities in the labor market in Europe - Kanas, Agnieszka; Fenger, Menno (Frontiers in Political Science, 2023)
Non-cognitive skills are increasingly essential in the labor market, especially given technological advances and evolving work environments. Unequal distribution of non-cognitive skills among various groups in the population may contribute to labor market inequalities. This article investigates the significance of non-cognitive skills for immigrant-native inequalities in the European labor market. Specifically, we examine the potential differences in non-cognitive skills between native and immigrant groups and how these differences may affect their income. Additionally, we explore whether equal levels of non-cognitive skills have comparable payoffs for native and immigrant groups in society. We use, comparative survey data from the Programme for the International Assessment of Adult Competencies and OLS regressions with country fixed effects. Our findings show that many immigrants exhibit lower levels of non-cognitive skills than native-born workers, despite differences between origin groups. This difference in non-cognitive skills explains part of the immigrant-native inequality in the labor market for most immigrant-origin groups. Moreover, our results indicate that immigrants, especially those from Central and Eastern European countries, benefit less from exercising comparable non-cognitive skills than native-born workers. Our study highlights the importance of non-cognitive skills in addressing the labor market disadvantage faced by immigrants, and emphasizes that policymakers and educators should recognize the significance of these skills when developing policies targeting immigrants.